Obsessive-compulsive disorder : current science and clinical practice - Zohar, Joseph (WPA series, evidence and experience in psychiatry (Unnumbered), 2012)
"A clear summary of what is known about a highly prevalent and debilitating disorder that affects nearly as many people as does asthma. Expert authors review the biological basis for the disorder and describe both pharmacological and psychological approaches to treatment"--Provided by publisher.